Adolescent Pregnancy and Its Problems - Karakuş, Savaş; Genç, Şerife Özlem; Güldemir, Ünsal; Okşaşoğlu, Buğra; Bütün, Celal; Yıldırım, Ali (The Bulletin of Legal Medicine, 2017)
Objective: The purpose of this study was to determine the adverse outcomes and pregnancy problems of adolescent pregnancy. Material and Method: Results of 171 adolescent pregnant between 10-19 age, who had given birth in our hospital between 2009 and 2016 were retrospective evaluated. The patients were seperated into adolescent early period (10-15 ages) and adolescent late period (>15-19 age). Babies,with birth weigt under 2500 gr were evaluated as low-birth-weight baby. The rates of gestational weeks, pregnancy history, preterm birth, Intrauterine mort fetüs (IUMF), preterm premature rupture of membranes (PPROM), preeclampsia and mode of delivery of groups were determined. Results: The age average of adolescent early period were determined as 14,6 ± 0,5, and the age average of adolescent late period were determined as 17,7 ± 0,5. In 3 cases (37.5 %) of adoscent early period and in 66 cases (40.5%) of adoscent late period were preterm birth and in adoscent early period were IUMF, PROM and preeclampsia without determination. Preeclampsia were determined in 5 cases (2.9%) IUMF, in 6 cases (3.7%) PPROM and in 4 cases (2.5%) in adolescent late period were. There was no significant difference in pregnancy weeks, obstetrical history, birth-weight and preterm delivery between two groups at birth. Conclusion: Because of Births, which come true during the adolescent period, create a serious problem by formation of healthy generations; it is a problem which have to be tackle carefully. Studies, which will done with large groups of adolescent pregnancy will give more informations on this topic.